2022
DOI: 10.3390/ijms24010249
|View full text |Cite
|
Sign up to set email alerts
|

Low Sulfur Amino Acid, High Polyunsaturated Fatty Acid Diet Inhibits Breast Cancer Growth

Abstract: Cancer cells may acquire resistance to stress signals and reprogram metabolism to meet the energetic demands to support their high proliferation rate and avoid death. Hence, targeting nutrient dependencies of cancer cells has been suggested as a promising anti-cancer strategy. We explored the possibility of killing breast cancer (BC) cells by modifying nutrient availability. We used in vitro models of BC (MCF7 and MDA-MB-231) that were maintained with a low amount of sulfur amino acids (SAAs) and a high amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…By understanding the specific alterations in lipid metabolism associated with different diseases, studies can develop targeted interventions to restore lipid homeostasis and mitigate disease progression. The potential of modulating lipid metabolism, such as targeting C5a/C5aR1 pathway in PD and lysosomal storage diseases [58,[87][88][89], ACAT1/SOAT1 inhibition in Alzheimer's disease [85], or modifying nutrient availability in cancer cells [70], opens new avenues for therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By understanding the specific alterations in lipid metabolism associated with different diseases, studies can develop targeted interventions to restore lipid homeostasis and mitigate disease progression. The potential of modulating lipid metabolism, such as targeting C5a/C5aR1 pathway in PD and lysosomal storage diseases [58,[87][88][89], ACAT1/SOAT1 inhibition in Alzheimer's disease [85], or modifying nutrient availability in cancer cells [70], opens new avenues for therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Turchi et al investigated the possibility of targeting nutrient availability as a complementary option for anti-cancer therapy, focusing on breast cancer models. By modifying the diet to be poor in proteins and sulfur amino acids while rich in oxidizable polyunsaturated fatty acids, the study revealed promising results in inhibiting breast cancer cell growth in vitro and in vivo [70]. Targeting the specific nutrient dependencies of cancer cells holds great potential for the development of personalized and effective therapeutic strategies.…”
Section: Unveiling the Complexities Of Lipid Metabolism In Cancer: Im...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a homemade fresh garlic extract has also been predicted to show anticancer activity, as it reduced tumor growth in preclinical mouse models with breast cancer [267]. Furthermore, a study from 2022 pointed to a low-sulfur amino acid diet as another possible inhibitor of breast cancer growth as it leads to decreased angiogenesis within the tumor mass as well as lower immune cell infiltrates and inflammatory cytokine production [268]. A lot of studies also focus on the iron-sulfur (Fe-S) clusters that form a protein, the nutrient deprivation autophagy factor-1, which is correlated with different cancer types [269][270][271][272].…”
Section: Sulfurmentioning
confidence: 99%